2006
DOI: 10.1159/000093665
|View full text |Cite
|
Sign up to set email alerts
|

The Frontal Assessment Battery Does Not Differentiate Frontotemporal Dementia from Alzheimer’s Disease

Abstract: Background: An early differentiation of Alzheimer’s disease (AD) from frontotemporal dementia (FTD) is important, since these conditions are essentially different regarding prognosis and therapeutical approach. Until now, no single test is available which allows a reliable differentiation. The Frontal Assessment Battery (FAB) has been found to have good reliability in identifying an executive deficit in frontal syndromes and in extrapyramidal disorders. The ability of the FAB to distinguish AD from FTD in mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 57 publications
5
50
1
Order By: Relevance
“…More specifi cally, bvFTD patients exhibited a more severe executive dysfunction, represented by their lower overall IFS scores compared with patients with AD. This difference becomes especially important when considering that the FAB's initially reported discriminant ability failed to be replicated by other research groups (Castiglioni et al, 2006 ;Lipton et al, 2005 ). The more severe executive dysfunction observed in patients with the bvFTD is consistent with the etiological properties of this condition: predominant frontal atrophy and executive disorders since the early stages (Hodges, 2001 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…More specifi cally, bvFTD patients exhibited a more severe executive dysfunction, represented by their lower overall IFS scores compared with patients with AD. This difference becomes especially important when considering that the FAB's initially reported discriminant ability failed to be replicated by other research groups (Castiglioni et al, 2006 ;Lipton et al, 2005 ). The more severe executive dysfunction observed in patients with the bvFTD is consistent with the etiological properties of this condition: predominant frontal atrophy and executive disorders since the early stages (Hodges, 2001 ).…”
Section: Discussionmentioning
confidence: 89%
“…The original authors conclude that the FAB is an easy-to-administer battery, sensitive to frontal dysfunction. By contrast, other studies have cast doubts on the sensitivity and specifi city of the FAB, and in particular, its ability to actually differentiate types of dementia, such as AD and FTD (Castiglioni et al, 2006 ;Lipton et al, 2005 ) in the early stages. Moreover, although the original study by Dubois et al ( 2000) showed no correlation between the FAB and general cognitive measures, subsequent studies failed to replicate these fi ndings suggesting that performance on the FAB does not refl ect frontal function exclusively (Castiglioni et al, 2006 ;Lipton et al, 2005 ).…”
Section: Introductionmentioning
confidence: 95%
“…We did not study the FAB because previous studies show that it does not differentiate bvFTD from AD (Castiglioni et al, 2006). Instead we chose to study associations with impaired functioning in 5 cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are unable to discriminate AD from FTD [32]. Despite the different pattern of brain damage, both groups showed a poor performance on Stroop's and Tower of London tests, secondary to an inhibitory dysfunction related to the disconnection within the network of cerebral areas recruited during the performance of these tests [33,34].…”
Section: Discussionmentioning
confidence: 94%
“…Although these appear more sensitive than cognitive testing in FTD [31], it also includes cognitive items [18]. The FAB [11] accurately discriminates between patients with frontal lobe dysfunction from normal controls, but the sensitivity and specificity to differentiate FTD from AD are not very high (77% and 87%, respectively) in mildly demented groups [14,32].…”
Section: Discussionmentioning
confidence: 99%